The Influence of Cognitive and Psychomotor Aspects on Students’ Academic Achievement - Anggriawan, Muhammad Verry; Efendi, Achmad; Damingun (Universitas Negeri Jakarta, 2025)
Background Many students struggle to understand complex academic material, which negatively impacts their academic performance Purpose This study aims to examine the influence of psychomotor and cognitive aspects on the academic achievement of management students at Muhammadiyah University of East Kalimantan. Design/method/approach This study uses a quantitative research design. Data were collected through structured questionnaires distributed directly to the selected students, as well as documentation of their academic records. The sample of 180 students was determined using the Slovin formula and selected by random sampling from a total population of 328 students. The collected data were analyzed statistically using SPSS 27 software, employing classical assumption tests, multiple linear regression, and hypothesis testing to assess the relationship between cognitive factors and academic achievement. Results The analysis revealed that cognitive aspects have a significant positive influence on the academic achievement of eighth-semester management students at Universitas Muhammadiyah Kalimantan Timur. Students who demonstrated stronger cognitive skills—such as critical thinking, understanding, and the ability to analyze material—tended to achieve higher academic performance, as reflected in their GPA and other academic indicators. The statistical results from multiple linear regression showed that the cognitive variable contributed meaningfully to variations in students’ academic success. These findings suggest that efforts to enhance cognitive abilities among students can lead to improved academic outcomes in higher education settings. Contribution/value This study provides valuable insight into the specific role of cognitive aspects in shaping academic achievement among eighth-semester management students at Universitas Muhammadiyah Kalimantan Timur. The findings offer practical recommendations for educators to design learning strategies that better support students’ cognitive growth.